Combinations of fibrinolytic gene polymorphisms (plasminogen activator inhibitor type 1 4G/5G, factor XIII Val34Leu and angiotensin-converting enzyme I/D) in women with idiopathic infertility. Issue 2 (18th March 2021) - Velickovic, Jelena; Jelicic, Mihajlo; Stojkovic, Oliver
Abstract : Supplemental Digital Content is available in the text Abstract : During normal pregnancy depressed fibrinolytic system is caused by changes in many factors, which could be influenced by different gene polymorphisms. The aim of this study was to investigate the combination of fibrinolysis-related gene polymorphisms in women with idiopathic infertility. We genotype polymorphisms 4G/5G in plasminogen activator inhibitor type 1 ( PAI- 1), Val34Leu in factor XIII ( FXIII ) and I/D in angiotensin-converting enzyme ( ACE ) gene. The patients group consisted of 83 females with idiopathic infertility, while the control group included 121 females with at least one born child. The alleles and genotypes distributions showed no significant differences between analyzed groups. Although higher frequency of PAI-1 5G5G genotype in patients did not reach statistical significance, 5G5G genotype of PAI-1 in combination with ValVal genotype of FXIII leads to higher risk for infertility ( P  < 0.05). In addition, when we added ACE I/D polymorphism in analysis, the 4G in PAI-1 and D allele in ACE, showed protective effect in combination with FXIII polymorphism ( P  < 0.05). The finding that combined homozygosity of 5G of PAI-1, commonly associated with greater fibrinolytic activity and bleeding tendency, in combination with Val genotype of FXIII impose a risk for female idiopathic infertility. The protective effect of alleles 4G ( PAI-1 ) and D ( ACE ) suggest that different combinations of polymorphisms influencing fibrinolysis could lead to better established hemostatic balance and reproductive success. Further analyses, with larger number of samples, as well as assessment of additional biochemical parameters of fibrinolysis, should be performed to clarify the role of gene polymorphisms on fibrinolysis and consequently their influence on reproductive success.